Prevalence of Shiga toxin–producing Escherichia coli and associated virulence genes in feces of commercial feedlot cattle - Cernicchiaro, Natalia; Cull, Charley A.; Paddock, Zachary Dean; Shi, Xiaorong; Bai, Jianfa; Nagaraja, Tiruvoor G.; Renter, David G. (My University, 2013)
The objective of this study was to determine the prevalence of Shiga toxin–producing Escherichia coli (STEC) serogroups and associated virulence genes in feces of commercial feedlot cattle. During March to May 2011, fecal samples were collected from individual cattle (n=960) in 10 cohorts (cattle subpopulations within a feedlot) comprising 17,148 total steers that originated from 48 backgrounding operations in six U.S. states. Fecal samples were enriched in E. coli broth and subjected to two detection protocols: (1) an 11-gene multiplex polymerase chain reaction (PCR) that identifies seven O serogroups (O26, O45, O103, O111, O121, O145, and O157) and four virulence genes (stx1, stx2, eae, and ehxA) applied to extracted total DNA (“direct PCR”); and (2) cultural procedures that involve immunomagnetic separation (IMS) with O26, O103, and O111 beads, plating on a nondifferential MacConkey agar, followed by the multiplex PCR of pooled colonies (“culture-based method”). Generalized linear mixed models were used to adjust prevalence estimates for clustering. Based on direct PCR detection, O157 (49.9%) was the most prevalent O serogroup followed by O26 (20.3%), O103 (11.8%), O121 (10.7%), O45 (10.4%), O145 (2.8%), and O111 (0.8%). Cumulative adjusted prevalence estimates were 22.3, 24.6, and 0.01% for O26, O103, and O111 serogroups, respectively, based on culture-based methods. However, prevalence varied significantly by cohort (p-values<0.05) for O26, O121, and O157 based on direct PCR, and for O26, O103, and O111 serogroups based on culture-based methods. Results of this study indicate that all seven STEC serogroups were identified in feedlot cattle feces, with O157, O26, and O103 being the most prevalent serogroups. A substantial proportion of serogroup-positive samples did not harbor Shiga toxin genes; thus, additional elucidation of the potential human health risk is required. Further evaluation of diagnostic methods for non-O157 STEC is needed given their impact on prevalence estimation.
Keywords: Escherichia coli; Shiga toxin; Feces; Cattle; Feedlot